Zakat and waqf as instrument of Islamic wealth in poverty alleviation and redistribution: Case of Malaysia. Issue 3 (17th September 2019) - Razak, Shaikh Hamzah Abdul
Abstract : Purpose: Zakat has a strong humanitarian and social-political value. Zakat occupies a central role in Islamic fiscal policy and operations. At the same time, it does not preclude the use of modern tools and techniques in raising the state revenues. Islam provides its own comprehensive approach how the state can raise its revenue and how the revenue should be spend. Zakat is collected from those who are qualified and distributed to the eight recipients as identified in the Quran. Waqf instrument plays an important role in Muslim societies as its support the aged, the poor, the orphans through provision of education, training and business activities. The creation of waqf is strongly advocated, especially the creation of cash waqf in view of the expensiveness of land as waqf . There are collaboration efforts for cash waqf and zakat collection being done through Islamic banks and takaful. The paper aims to discuss these issues. Design/methodology/approach: The data were source from the inland revenue, government agencies and state religious authorities, interviews, articles and conference reviews, as well as economic reports and later transcribe into charts and figures. Findings: Its shows the efficiency of wealth distribution according to the Islamic principles and application of the financial inclusion in the Islamic society. Research limitations/implications: The limitation is in verifying the accuracy of data gathering from the government agencies. Social implications: The study can be used in financial inclusion through the application of zakah and waqf being applied to alleviate poverty. Originality/value: The research is an extended work done on zakah and waqf in Islamic wealth distribution.